Baló Concentric Sclerosis. Issue 1 (31st October 2022) - Di Dier, Kelly; Lemmerling, Marc
Teaching Point: Baló concentric sclerosis is a rare subtype of multiple sclerosis, characterized by a concentric layered mass on magnetic resonance imaging.